CONDITIONS THAT INFLUENCE CHILDREN’S POPULARITY AMONG PEERS - NAPORA, ELŻBIETA (Studia Psychologica: Theoria et praxis, 2016)
The purpose of this study was to determine which factors influence varied popularity of children among their peers. It was expected that the traits of the child and its family will affect both the positive and the negative reactions of the peers, and that they will influence the type of the child’s popularity in the group. The sample for the current study included 192 students aged 11–13. Moreno’s sociometric test was used to conduct the study. The results showed that the material situation of the family is related to the child’s popularity in the group, as children tend to like more those from well-to-do families. Lower economic status is more frequently observed in incomplete families and is perceived much more negatively by boys than by girls. The obtained results should be analyzed from the point of view of a broader context of social issues caused by the differences in the families’ incomes. The results of the study suggest that children from wealthy families are not only more popular among their peers, but they also perform better academically and have better prospects of reaching their goals.